ANALISIS PERBANDINGAN KINERJA KARYAWAN PT. PLN (PERSERO) ULP CILEDUG SEBELUM DAN MASA PANDEMI COVID-19 DALAM SUDUT PANDANG MANAJEMEN SYARIAH - Riyani, Desti Amanda; Suryani, Ermi; Shiddieqy, Hasbi Ash (Sahid Business Journal : Jurnal Penelitian Manajemen Bisnis Syariah: Program Studi Manajemen Bisnis Syariah, 2023)
During the current global pandemic, numerous sectors have undergone significant transformations, including the economic realm. Almost all companies have had to adapt their operations to cope with the challenges brought about by the pandemic. One prevalent response has been the implementation of Work From Home (WFH) arrangements. Undoubtedly, human resources constitute the most influential asset within a company, as their performance directly affects the organization's success. Thus, the aim of this study was to assess and compare the performance of employees at PT. PLN (Persero) ULP Ciledug before and during the Covid-19 pandemic, while also exploring the perspectives of Islamic management on employee performance during this unprecedented period. The research approach employed was descriptive qualitative, involving the analysis of gathered data to draw well-founded conclusions. Primary and secondary data were collected through interviews and documentation, specifically utilizing the Employee Performance Management Information System (SIMKPNAS) at PT. PLN (Persero) ULP Ciledug. The findings and analyses derived from this study revealed notable disparities in the performance of PT. PLN (Persero) ULP Ciledug employees prior to the Covid-19 outbreak. Based on the Key Performance Indicators (KPIs), employees generally displayed a high level of performance, with an average competence rating of 2, indicating that they exceeded expectations or met requirements (ER). However, during the Covid-19 pandemic, there was a slight decline in employee performance at PT. PLN (Persero) ULP Ciledug, particularly in competencies 2 and 3, corresponding to the "Exceeding Expectations" / Exceeds Requirements (ER) and "Meeting the Requirements" (MR) categories. It is important to note that the performance of employees at PT. PLN (Persero) ULP Ciledug, both before and during the Covid-19 pandemic, adhered appropriately to the principles of Sharia management, as aligned with Islamic values.